Update on Pharmaceutical and Minimally Invasive Management Strategies for Chronic Obstructive Pulmonary Disease - Rafii, Rokhsara (Hindawi Publishing Corporation, 2011)
Chronic obstructive pulmonary disease (COPD) is a debilitating pulmonary disorder with systemic effects, and it is the fourth leading cause of death in the United States. COPD patients not only develop respiratory limitations, but can also demonstrate systemic wasting, features of depression, and can succumb to social isolation. Smoking cessation is crucial, and pharmacotherapy with bronchodilators is helpful in symptom management. Inhaled corticosteroids may be beneficial in some patients. In addition, pulmonary rehabilitation and palliative care are important components under the right clinical circumstance. This review highlights current guidelines and management strategies for COPD and emphasizes novel pharmacotherapy and minimally invasive (nonsurgical) lung-volume reduction interventions that may prove to be of significant benefit in the future.